The Development of the Temperature Disturbance Zone in the Surrounding of a Salt Cavern Caused by the Leaching Process for Safety Hydrogen Storage - Leszek Pająk; Leszek Lankof; Barbara Tomaszewska; Paweł Wojnarowski; Damian Janiga (Energies, 2021)
This article presents an estimation of the temperature decrease in the vicinity of a salt cavern due to its leaching. The one-dimensional radially symmetry models of a salt cavern were considered and described. The initial temperature of rock salt massif was assumed as 50 <semantics>∘</semantics>C and temperature of leaching water varied seasonally from 6 <semantics>∘</semantics>C to 20 <semantics>∘</semantics>C. A significant influence of the season of the leaching process, beginning on the final temperature distribution was found. The model takes into account: convection coefficient changes depending on temperature of brine and rock formation and heat effects caused by salt dissolution. Numerical results are compared with measurements data on the field of cavern volume increasing with time as the function of flow of leaching water and its temperature. The accuracy of the cavern volume increasing versus time was assumed as good—both quantitative and qualitative.